Bioinformatics: A Concept-Based Introduction - Mathura, Venkatarajan S.; Kangueane, Pandjassarame; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
Bioinformatics: A Concept-Based Introduction is provides a balance of information on computational methods and biological information. Instead of delving in depth, a broad but necessary overview is provided for each topic, resulting in content that will benefit readers with different levels of expertise. This book contains contributions from experts in the field on emerging topics like Immunoinformatics, Genomics and Proteomics. It discusses real-world problems with Bioinformatics solutions, cites important URLs and contains selected chapter exercises to reinforce concepts.
to Biological Systems -- Computer Programming Fundamentals and Concepts -- to Algorithms -- Biological Sequence Databases -- Biological Sequence Search and Analysis -- Protein Structure Prediction -- Protein-Protein Interaction and Macromolecular Visualization -- Genes, Genomics, Microarray Methods, and Analysis -- to Proteomics -- Biomedical Literature Mining -- Computational Immunology: HLA-peptide Binding Prediction -- Bioinformatics Application: Eukaryotic Gene Count and Evolution -- Bioinformatics Application: Predicting Protein Subcellular Localization by Applying Machine Learning -- Bioinformatics Analysis: Gene Fusion.
Keywords: LIFE SCIENCES; BIOINFORMATICS; LIFE SCIENCES; BIOINFORMATICS